Judicial Oversight of the Administrative Court over the Appropriateness of Expropriation Decisions for Public Benefit - Wael Faraj Elmatoni (Journal of Scientific and Human Dimensions, 2026)
This study examines the administrative judiciary’s oversight of expropriation decisions for public benefit. Although property ownership is legally protected in most legal systems, the State may, in certain cases, expropriate private property to serve the public interest. Such actions, however, must not be arbitrary or abusive. To safeguard property rights, the legislator empowers the administrative judiciary to review and monitor the legality and appropriateness of expropriation decisions. The research emphasizes that the authority to expropriate is not absolute; it must be exercised strictly within the limits of achieving genuine public benefit. Moreover, administrative bodies are required to ensure a balance between the harm resulting from depriving individuals of their property and the benefits derived from the expropriation. The study concludes that effective judicial oversight is essential to prevent misuse of administrative power and to uphold justice and fairness in the implementation of public benefit projects